2008 IEEE International Symposium on Wireless Communication Systems 2008
DOI: 10.1109/iswcs.2008.4726053
|View full text |Cite
|
Sign up to set email alerts
|

Experimental characterization of the body-coupled communications channel

Abstract: Abstract-Body-coupled communications (BCC), in which the human body is used as a communications channel, has been shown to be a promising solution for wireless body-area networks (WBANs). For successful deployment of these BCC-based WBANs, it is necessary to develop a clear understanding of the channel behavior. Therefore, this paper presents the key characteristics of the capacitively-coupled on-body channel used for BCC. This is based on an experimental study, which was carried out with a specifically design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 11 publications
0
39
0
Order By: Relevance
“…The other option is using a sensor with very high input impedance to detect small displacement currents [50,79]. We refer the reader to additional literature on the various aspects of grounding [68,100,176,202].…”
Section: Sensitivity To Groundingmentioning
confidence: 99%
See 1 more Smart Citation
“…The other option is using a sensor with very high input impedance to detect small displacement currents [50,79]. We refer the reader to additional literature on the various aspects of grounding [68,100,176,202].…”
Section: Sensitivity To Groundingmentioning
confidence: 99%
“…Equivalent circuit models can quickly become more complex when environmental effects, such as grounding [34] or wet skin [227] are considered. Several papers have shown that the human body reacts similarly to different frequencies [7,22,100], though Schenk et al point out that it is hard to obtain such data with statistical significance [176]. There are no indications that the electric fields typically used in capacitive sensing systems have adverse effects on users' health [71,235].…”
Section: Modeling and Physical Understandingmentioning
confidence: 99%
“…For galvanic coupling, these electrodes need to be placed on the skin directly. For capacitive coupling, there is no need for a direct human skin contact [17], unless, then close proximity of the coupler to the body is required. These electrodes can be structured horizontally or vertically where the spacing between them is filled with a dielectric material.…”
Section: The Body Couple Communication (Bcc) Technologymentioning
confidence: 99%
“…Until unless there are scenarios where information is shared amid people via physical contact. These are very diverse applications and each of these have very [20] and second intrabody communication. The division between interbody and intrabody is the most fundamental differentiator for technical reasons for connecting devices by traversing two people is technically harder to achieve with reasonable performance.…”
Section: How Can Body Coupled Communications Be Usedmentioning
confidence: 99%
“…According to their measurements, human body behaves as a single-pole high pass filter with cut-off frequency at 4 MHz and above 10 MHz the behavior of human body changes with frequency and distance. Schenk [15] of Philips research group presented comprehensive experimental measurement results for capacitive BCC channel as a function of different electrode configurations, human subjects and test conditions using battery operated transmitter/receiver and portable measuring instruments. Their experimental results show that the worst case body attenuation could be 80 dB for given configuration/scenario in the frequency region of 100 kHz to 60 MHz.…”
Section: Introductionmentioning
confidence: 99%